ACTIVATING EFL LEARNERS BY INTEGRATING TEAM-BASED LEARNING WITH COLLABORATIVE STRATEGIC READING - Khadijah Maming (LITERA, 2019)
Team-Based Learning (TBL) is one of active learning strategies that build on individuals’ strengths by allowing them to collaborate and work as a team to achieve common learning objectives. TBL is a cooperative learning strategy was introduced to encourage students become active learners rather than be passive recipients of information. It is generally based on the principle that students working together as a cohesive team are able to achieve higher levels of learning. The lecturer’s role essentially is as facilitator. In order to activate the participation of EFL learners in classroom and improve their reading comprehension ability, the researcher conducted a research to find out good impacts of TBL integrated with Collaborative strategic reading toward the English Education Department students in Indonesia as EFL learners. The researcher applied quasi-experimental method. The students started reading activity by previewing the text, click (what vocabulary the students understand), clunk (what vocabulary the students don’t understand), getting the gist, wrapping up and done cooperatively. The conclusion of this research showed that TBL integrated with Collaborative strategic reading can activate the participation of EFL learners in classroom and improve their reading comprehension ability. It also had better achievement than the students taught by conventional learning. Keywords: team-based learning, collaborative strategic reading, EFL, active learning